PENINGKATAN HASIL BELAJAR SMASH BOLA VOLI MELALUI PERMAINAN PUBOGA DALAM PENJASORKES SISWA KELAS V SD N KARANGANYAR 01 KEC. TUGU KOTA SEMARANG TAHUN PELAJARAN 2012/2013 (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2013)
The problems that exist in SD N Karanganyar 01 excl. Tugu city of Semarang is less teacher applyingvariations in teaching or monotonous, so students difficulties in learning volleyball especially in basic motionsmash (hit) and the student happened saturated and spirit so that many students who do not meet the criteriaspecified minimum passing grade schools to 75, from 44 students in the class V SD N Karanganyar 01 excl.Semarang city monument only 28 students (63.63%) who completed the study, while students who did notcomplete as many as 16 students (36.36%). Research objectives were to improve student learning outcomes andfoster interest in making learning a fun, active, innovative and creative. This type of research in this research isa class act. In this study using grade V SD N Karanganyar 01 excl. Semarang city monument which totaled 44 siswa.Teknik collecting observational data using student activity sheets that include cognitive, affective andpsychomotor and practice tests. The technique uses descriptive qualitative data analysis. From the results ofresearch in the classical cycle of data that I obtained in the classical mastery learning students who achievecomplete as many as 20 students or 45.45%, and students who have not completed as many as 24 categories ofstudents or 54.54%). As for the second cycle of data obtained in the classical mastery learning students whoachieve complete as many as 44 students or 100%, and students who have not completed as much as category 0or students (0%). From the research cycle I to cycle II has been an increase in the classical high of 24 students(45.45%) increase learning outcomes, it can be concluded that the increase in learning outcomes smash gamevolleyball game approach puboga in class V SD N Karanganyar 01 successful . The conclusion of this researchis a learning approach to smash a volleyball game at throwing a rubber ball can improve student learningoutcomes. Researchers also proposed suggestions are: 1) to improve student learning semnagat bdalalm anyconditions, because learning is fun game with the media, and 2) those teachers are expected to take advantageof the game throwing a rubber ball at the school to provide a fun learning process for students .